PSYCHOLOGICAL METHODS OF PSYCHOLOGICAL PREPARATION OF MILITARY PERSONNEL FOR MILITARY DISCIPLINE IN COMBAT SITUATIONS - Xamraev Laziz Erkinovich (American Journals, 2022)
In this article, psychological methods of psychological preparation of military personnel for military discipline in combat situations were discussed.
Keywords: military discipline, psychological method, combat factors, motivation, component, cognition.